Adp-ribosyl cyclase and cyclic ADP-ribose hydrolase act as a redox sensor. a primary role for cyclic ADP-ribose in hypoxic pulmonary vasoconstriction. - Wilson, H; Dipp, M; Thomas, J; Lad, C; Galione, A; Evans, A (2001)
Hypoxic pulmonary vasoconstriction is unique to pulmonary arteries and serves to match lung perfusion to ventilation. However, in disease states this process can promote hypoxic pulmonary hypertension. Hypoxic pulmonary vasoconstriction is associated with increased NADH levels in pulmonary artery smooth muscle and with intracellular Ca(2+) release from ryanodine-sensitive stores. Because cyclic ADP-ribose (cADPR) regulates ryanodine receptors and is synthesized from beta-NAD(+), we investigated the regulation by beta-NADH of cADPR synthesis and metabolism and the role of cADPR in hypoxic pulmonary vasoconstriction. Significantly higher rates of cADPR synthesis occurred in smooth muscle homogenates of pulmonary arteries, compared with homogenates of systemic arteries. When the beta-NAD(+):beta-NADH ratio was reduced, the net amount of cADPR accumulated increased. This was due, at least in part, to the inhibition of cADPR hydrolase by beta-NADH. Furthermore, hypoxia induced a 10-fold increase in cADPR levels in pulmonary artery smooth muscle, and a membrane-permeant cADPR antagonist, 8-bromo-cADPR, abolished hypoxic pulmonary vasoconstriction in pulmonary artery rings. We propose that the cellular redox state may be coupled via an increase in beta-NADH levels to enhanced cADPR synthesis, activation of ryanodine receptors, and sarcoplasmic reticulum Ca(2+) release. This redox-sensing pathway may offer new therapeutic targets for hypoxic pulmonary hypertension.